Comparison of the Protective Effects of Nebivolol and Metoprolol against LPS-Induced Injury in H9c2 Cardiomyoblasts - Rukhsana Gul; Meshail Okla; Amer Mahmood; Shahid Nawaz; Amina Fallata; Arwa Bazighifan; Musaad Alfayez; Assim A. Alfadda (Current Issues in Molecular Biology, 2023)
Here, we, for the first time, compared the cardioprotective effects of third-generation vasodilating beta-blocker nebivolol (Neb) and conventional beta-blocker metoprolol (Met) on LPS-induced injury in H9c2 cardiomyoblasts. Our findings denoted that Neb and Met pretreatment diminish LPS-mediated cytotoxicity and oxidative stress. Concomitantly, LPS-triggered inflammatory cytokines activation was significantly suppressed by Neb but not by Met. Pretreatment with either Neb or Met alleviated LPS-mediated mitochondrial impairment by enhancing the expression of genes related to its biogenesis such as PGC-1α, NRF1, and TFAM. On the contrary, Neb but not Met-upregulated mitochondrial fusion-related genes such as OPA, and MFN2. In summary, our findings suggest that Neb and Met treatment significantly ameliorated the LPS-induced cytotoxicity and oxidative stress. Additionally, these findings suggest that Neb but not Met significantly down-regulates LPS-induced proinflammatory factors, probably by enhancing mitochondrial biogenesis and fusion.